Avaliação de marcadores externos e internos para estimar excreção fecal e/consumo em ovinos alimentados com pastagem natural ou feno de Tifton 85 - Longo, Thaís Regina (2015)
The objective of this study was to evaluate the external markers chromium oxide (Cr2O3), titanium dioxide (TiO2) to estimate fecal recovery, fecal excretion, time to become constant and totally disappear from the animal's body and sampling time effect throughout the day; and internal markers indigestible dry matter (iDM), indigestible neutral detergent fiber (iNDF) and fecal nitrogen (FN) to estimate nutrient digestibility and intake of organic matter in sheep. Six Corriedale lambs were fed diets base of Tifton 85 hay (TH) or natural pasture (NP), in a Latin square design (3 x 3). The animals were dosed once daily with TiO2 and Cr2O3. Daily fecal samples were taken from the first day of each period and in the last four days stool samples were obtained at different times throughout the day. The iDM and iNDF were evaluated by weighing in polyester bags food and faeces and incubated in situ for 144 hours. For the stabilization of the TiO2 marker fecal excretion was 9 days after the first dose and fecal recovery of 72% for longer Cr2O3, this stabilized at 10 days and faecal recovery was 84%. The iDM showed recoveries of 100% (TH) and 91% (NP) and iNDF 92% (TH) and 71% (NP), having high and significant relationship to estimate OMD. For the NF was also observed high and significant relationship between observed and NF estimated OMI, with coefficients of determination of 75% for FT and 58% for PN. Thus, the TiO2 and Cr2O3 not show full recovery and fecal both showed high variability throughout the day or on different days, requiring at least 10 days prior to delivery. However, iDM is a suitable marker to estimate the digestibility of forage. Similarly, in animals that is made complete collection of feces, N Faecal excretion is an appropriate indicator for estimating consumption OM.